PENYAJIAN RUANG NARATIF DAN IMPLIKASI MAKNANYA PADA NOVEL JR UENO EKI KOUEN GUCHI KARYA YU MIRI - Ananda, Dika Dean; Adji, Muhamad; Saleha, Amaliatun (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2024)
Not only as a background to the plot, space can also be used as the center of the story or act as a helper for the story.  Space can also have symbolic meaning that plays a role in enriching the world of the story.  This research discusses the narrative space in the Japanese novel JR Ueno Eki Kouen Guchi (2014) by Yu Miri.  In this novel, space is the main driver of the story.  This research aims to explain narrative space strategies using the spatial narratology perspective described by Ryan, Foote, and Azaryahu (2016).  The research results show that the construction of space in this novel shows the existence of certain patterns that build the world in the story.  This pattern shows the implication of meaning through the relationships between spaces.  This relationship provides context for the actions taken by the characters and the events that appear in the novel.  Through space construction, the circumstances surrounding the entire text can be identified.  This shows that narrative space constructs the world in the novel by providing context for the things that happen in the story plot.Keywords: narratology, narrative space construction, JR Ueno Eki Kouen Guchi